Analisis Pengaruh Keragaman Produk Lokasi dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Toko Kanaan di Kelurahan Kolana Utara Kecamatan Alor Timur Kabupaten Alor - Yusuf Makena (Peneliti.net, 2023)
Purchasing decisions are actions taken by consumers to buy or not to a product. Purchasing decisions are the focus of every company because purchasing decisions will determine the company's success in marketing its products. This study aims to determine the effect of product diversity, location and service quality on purchasing decisions. This type of research is a quantitative research with data collection techniques, namely observation, interviews, and documentation studies. This study uses population primary data and the sample is consumers who come to make purchases at the Kanaan store in Kolana Utara Village, East Alor District, Alor Regency, totaling 30 people. And the sampling technique in this study is a saturated sample. The statistical method used in this study is multiple linear regression this shows that: (1). partially the product diversity variable has a significance value of 0.000 or 0.0% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H1 which states that the product diversity variable partially has a positive effect on purchasing decisions in Kanaan shop in North Kolanan Village, East Alor District, Alor Regency. (2). partially the location variable has a significant value of 0.001 or 0.1% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H2 which states that the location variable partially has a positive effect on purchasing decisions at Kanaan Stores In North Kolanan Village, East Alor District, Alor Regency (3). partially the variable of service quality has a significant value of 0.005 or 0.5% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H3 which states that the variable quality of service partially has a positive effect on purchasing decisions in Kanaan shop in North Kolanan Village, East Alor District, Alor Regency. (4). simultaneously the variable product diversity, location and service quality on purchasing decisions for this type of research has a significant value of 0.000 or 0.00%, where this value is smaller than the alpha value, which is equal to 0.05, namely 5% so that the results of this study simultaneously receive H4 which states that the variables of product diversity, location and service quality on purchasing decisions of this type of research simultaneously have a positive effect on purchasing decisions at Kanaan Stores in North Kolanan Village, East Alor District, Alor Regency. (5). The magnitude of the influence of the variable location product diversity and service quality on purchasing decisions for this type of research is 82.5%, this study simultaneously accepts H5.